Agriculture and Livestock in Oman through the books of travelers and ‎countrymen from the third century AH to the eighth century AH - noor bassem Mohammed; Abduljabbar M. Shrems (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: This study aims to provide a clear picture of agriculture and livestock wealth in Oman through the accounts of travelers and historians. It also examines the descriptions of travelers such as Ibn Khurdadhbeh, al-Yaqoubi, al-Baladhuri, al-Hamdani, al-Istakhri, al-Masudi, Ibn Hawqal, al-Muqaddasi, al-Idrisi, al-Hamawi, Ibn Khaldun, and others by focusing on Oman’s geography and the peoples who inhabited the region in ancient times. Methodology: The current study employed the historical-descriptive and analytical approach to highlight the importance of agricultural and livestock wealth in Oman. The study offered a clear descriptive image of these resources, detailing their significance, quantity, types of crops grown, and the farming and irrigation methods used in Oman. Results: After analyzing the data, the results showed that the study provided a clear image of the agricultural and livestock activities in Oman based on the accounts of geographers and travelers, ranging from the 3rd to the 9th century Hijri. The study also showed that the writings of geographer-travelers served as crucial sources that supplement historical records, filling gaps in our knowledge. The study also showed that Oman is one of the countries that received significant attention from geographer-travelers who visited it. Conclusion: It can be concluded that Oman’s agricultural products were diverse, and this variety led to an abundance of production, which had a notable impact on Oman’s economy. Additionally, livestock wealth flourished in Oman due to the region’s natural environment, which was well-suited for animal breeding.